The Innovation Paradox in Public Procurement: A Systematic Review and Conceptual Taxonomy - Pross Oluka Nagitta; Gracious Jean Ampumuza; Robert Agwot Komakech; John Michael Maxel Okoche; Peter Adoko Obicci (International Journal of Supply Chain Management, 2026)
Public procurement is increasingly recognized as a strategic policy instrument for stimulating innovation, addressing societal challenges, and creating public value. Despite growing policy support and scholarly interest, the implementation of innovation-oriented procurement remains uneven, with public organizations frequently struggling to translate innovation ambitions into practice. This study systematically reviews the literature on Public Procurement Innovation (PPI) to identify the drivers and constraints influencing innovation-oriented procurement, examine the conditions shaping its implementation, and explain the persistence of the innovation paradox. Drawing on Institutional Theory and Innovation Systems Theory, the study employs a systematic literature review methodology to analyse 133 peer-reviewed articles published between 2006 and 2024 and indexed in the Scopus database. The findings reveal that innovation procurement outcomes are shaped by four interrelated dimensions: institutional conditions, regulatory frameworks, organizational capabilities, and market dynamics. Policy commitment, governance coordination, flexible procurement instruments, organizational competencies, supplier engagement, and supportive innovation ecosystems emerge as important enablers of innovation-oriented procurement. Conversely, fragmented governance structures, procedural rigidity, capability deficits, risk aversion, information asymmetries, and weak market responsiveness frequently constrain implementation. The review demonstrates that innovation outcomes depend not on individual factors alone but on the alignment of conditions across these dimensions. The study contributes to the literature by advancing a multidimensional explanation of the innovation paradox in public procurement and developing a conceptual taxonomy that integrates institutional, regulatory, organizational, and market perspectives into a unified analytical framework. The findings offer theoretical insights into the governance of innovation-oriented procurement and practical implications for policymakers and procurement practitioners seeking to strengthen innovation outcomes through public procurement.